Estimation of the seminal fluid of subfertile patients of different age groups. - Harmoosh, Shima K.; Almadfaiee, Zaid A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Among different lifestyle factors, aging process can adversely affect male semen parameters and hence male fertility in this study, semen parameters and productive hormonal profiles of subfertile young men were compared with subfertile middle and old age men.